2021
DOI: 10.2147/cmar.s313123
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Pretreatment Peripheral Neutrophil-to-Lymphocyte Ratio for Response to Neoadjuvant Chemotherapy and Breast Cancer Prognosis

Abstract: Background Neutrophil-to-lymphocyte ratio (NLR) is connected with the response to neoadjuvant chemotherapy (NAC) and prognosis. In addition, residual lymph node burden after NAC is likely important for prognosis. However, most studies have focused on the predictive value of NLR for NAC pathological complete response (pCR) rate. The relationship between NLR and post-operative residual lymph node ratio (LNR), and their prognostic values remain to be determined. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Of the 12 studies, 10 studies reported OS and 11 reported DFS. With regard to the study area, four studies were conducted in Chinese ( 10 , 19 , 22 , 27 ), while the remaining nine studies were conducted in non-Chinese countries. The median follow-up ranged from 24 to 87 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 12 studies, 10 studies reported OS and 11 reported DFS. With regard to the study area, four studies were conducted in Chinese ( 10 , 19 , 22 , 27 ), while the remaining nine studies were conducted in non-Chinese countries. The median follow-up ranged from 24 to 87 months.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 13 eligible studies, 10 studies ( 9 11 , 18 , 21 , 23 27 ) explored the association between LNR and OS outcomes. Meta-analysis has demonstrated that a significant correlation between higher LNR and shorter OS of breast cancer patients received neoadjuvant chemotherapy (HR: 4.74; 95%CI: 3.36–6.67; P < 0.001) with significant heterogeneity ( I 2 = 57.2%; P = 0.013) ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] As for those who receiving neoadjuvant chemotherapy, especially with luminal and triple-negative tumors, high pretreatment NLR level usually meant lower pathological complete response rate and worse survival. [22–24] The predictive value of this negative correlation was also expressed in breast cancer patients who underwent local surgical treatment directly. Kim et al [25] found that NLR was associated with poor prognosis among triple-negative breast cancer patients, while the increasement of NLR during treatment compared to the preoperative status may suggest the need for additional treatment besides the routine medical therapy.…”
Section: Discussionmentioning
confidence: 99%